Assistance for coffee processing into kombufee with fermentation method in Benjor Village - Juwita, Ratna; Manggara, Algafari Bakti; Mizar, Muhammad Alfian; Istiqomah, Aisyah Shabrina; Lathifah, Listy Nailah Mahdiyyatul; Hamni, Septiani Dewi (Talenta Publisher Universitas Sumatera Utara, 2025)
Benjor Village, located in Malang Regency, is one of the largest Arabica coffee producing areas in East Java, has great potential in the development of processed coffee products, but still has limitations in terms of innovation. Currently the community only sells coffee in raw form or coffee powder. This service activity aims to increase the added value of Benjor Village Arabica coffee through the innovation of kombufee beverage products. This drink is produced from fermentation of Arabica coffee with kombucha culture, making it rich in probiotics and antioxidants. The target in this activity leads to the productive economic sector of mothers of Family Welfare Empowerment Benjor Village.The method of implementing this service activity is carried out by training and mentoring the processing of Arabica coffee into kombufee using the fermentation method. The results of the training and mentoring were an increase in partner skills, such as mothers of Family Welfare Empowerment in Benjor village, in the contents of kombufee made from coffee beans by 72%. Mentoring activities were carried out for two months, both offline and online (using Whatsapp Group) so that the trainees were able to make kombufee independently and were suitable for sale. Kombufee processing training to the community, especially mothers of Family Welfare Empowerment, is expected to encourage community economic independence and introduce high-value local products.